On the possibility of using small asteroids for deflecting near-Earth asteroids. Issue 8 (15th April 2016) - Akiyama, Yuki; Bando, Mai; Hokamoto, Shinji
Highlights: A kinetic impactor mission to deflect PHAs using an intermediate asteroid is studied. The Δ V for the sequential trajectory to yield a chain collision is formulated. The characteristics of the optimal trajectory are revealed. Efficient selection strategy of an intermediate asteroid is proposed. Abstract: This paper presents the trajectory design and analysis of the near-Earth asteroid (NEA) deflection mission enabled by a kinetic impact of an intermediate asteroid. The sequential transfer trajectory is designed by solving two Lambert's problems that yield a chain collision between a spacecraft and an intermediate asteroid, followed by a collision between the intermediate asteroid and an NEA. The characteristics of the low-cost trajectories are then identified with respect to the optimal collision point. We show that the feasibility of the mission depends on the existence of an intermediate asteroid with small minimum orbit interception distance (MOID) with the NEA. Moreover the selection strategy of an intermediate asteroid that makes the mission feasible is discussed. We show that several asteroids exist that allow a 10 ton spacecraft with limited Δ V to be launched and impact the NEA 99442 Apophis allowing a deflection given several years warning time.